Successful Management of Hemolytic Anemia Due to Rh-immunization, Diagnosed Antenatally - Sevinch Mahmudova; Gulnar Elizade; Nezrin Hesenli; Turab Janbakhishov; Sarkhan Elbayiyev (Caucasian Medical Journal)
Hemolytic disease of the fetus and newborn (HDFN) remains a significant concern in maternal-fetal medicine, despite advancements in prevention and management. HDFN occurs when maternal alloimmunization leads to the production of immunoglobulin G (IgG) antibodies that cross the placenta and trigger fetal red blood cell hemolysis. Severe HDFN can cause hydrops fetalis and fetal death if left untreated, whereas survivors often face complications like neonatal anemia and hyperbilirubinemia, potentially causing kernicterus. A 42-year-old Rhesus (Rh)-negative woman with Rh-positive fetal anemia underwent intrauterine transfusions at 23 and 29 week of gestation. The fetus received Rh-negative donor blood during cordocentesis, which led to improvement in hemoglobin levels and normalization of Doppler parameters. Delivery at 34 weeks was via cesarean section because of premature membrane rupture. Postnatal management included exchange transfusion, phototherapy, and Ig therapy, resulting in stabilized hemoglobin and bilirubin levels. This case highlights the critical role of antenatal and postnatal interventions in managing severe HDFN. Regular monitoring and timely intervention, including Doppler ultrasound for anemia assessment and transfusion strategies, can significantly improve outcomes for high-risk neonates.